Effect of Covid-19 pandemic on gender associated with risk factors: a retrospective data analysis, Thailand - Jadsada Kunno; Busaba Supawattanabodee; Chavanant Sumanasrethakul; Budsaba Wiriyasirivaj; Sathit Kuratong; Chuthamat Kaewchandee; Pataraporn Yubonpunt (National Institute of Public Health - National Institute of Hygiene, 2022)
Background. The COVID-19 pandemic is having a serious impact around the world. Many countries have experienced a two or three wave pattern in reported cases. The virus's spread in Thailand was a cluster event distributed over multiple locations, multi-spender, and multiple waves of outbreaks. Objective. This study aims to study gender associated with age, risk factors, and nationality during coronavirus pandemic in Thailand. Material and methods. A retrospective cohort study was conducted from January 2020 to May 2021 (17 months) to determine the number of confirmed cases and identify gender associated with, age, various risk factors and nationality were analyzed by chi square test and binary logistic regression analyses. Results. The results show that the number of cases increased by over 100,000 over the course of three waves of outbreaks. The logistic regression analysis revealed that genders were significantly related with age, various risk factors, and nationality across different waves (p < 0.01). Across the primary risk factors were community risk, community cluster and close contact with a previously confirmed patient on confirmed cases during COVID-19 pandemic. Conclusion. Significant differences between genders were significantly associated with age, various risk factors, and nationality may be due to weak social distancing policies and the lack of public health interventions. A COVID-19 vaccination plan is needed for people who are at risk of suffering severe symptoms as well as the general population in outbreak areas to increase immunity.